An Analysis of Rural Land transfer in China - Tian, Mengxiao (International Journal of Natural Resources and Environmental Studies, 2025)
The transfer of rural land is of great significance in achieving large-scale operation, promoting technology application and industrial chain optimization, and increasing farmers’ income. This article analyzes the practical significance of rural land transfer and explores the main problems that constrain land transfer, such as the lack of land transfer service platforms, non-standard transfer procedures, and low willingness of farmers to transfer. Targeted solutions are proposed to these problems, aiming to promote the healthy and orderly development of rural land transfer and assist in the implementation of the rural revitalization strategy.